2021
DOI: 10.3389/fpls.2021.617873
|View full text |Cite
|
Sign up to set email alerts
|

Common Vetch, Valuable Germplasm for Resilient Agriculture: Genetic Characterization and Spanish Core Collection Development

Abstract: Common vetch (Vicia sativa L.) is a legume used for animal feed because of its high protein content and great capacity for nitrogen fixation, making this crop relevant in sustainable agriculture. The Spanish vetch collection, conserved at the Spanish Plant Genetic Resources Center (CRF), is one of the largest collections of this species worldwide, including landraces, wild relatives mainly collected in Spain, and commercial cultivars, but also accessions of international origin. The analysis of the genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…The total number of common vetch populations is quite difficult to estimate, as this specie was distributed worldwide. More than 20,000 accessions were kept in the plant genetic resources (PGR) [ 2 ]. It is difficult for farmers to directly use or incorporate into breeding programmes due to the large number of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of common vetch populations is quite difficult to estimate, as this specie was distributed worldwide. More than 20,000 accessions were kept in the plant genetic resources (PGR) [ 2 ]. It is difficult for farmers to directly use or incorporate into breeding programmes due to the large number of germplasm resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, the genetic information of common vetch remains largely unknown, although some studies have performed transcriptome analysis, genetic diversity analysis with ESTs based on SSR markers, and EMS-induced mutation development [2,[5][6][7]. Nevertheless, the genomic information regarding common vetch currently remains unavailable, as well as the systematic analysis of Chinese common vetch germplasm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation analysis shows that organic matter, total nitrogen and available potassium in kiwifruit rhizosphere soils were positively correlated with their bacterium number, actinomycete number, sucrase activity, urease activity and phosphatase activity, and available phosphorus was positively correlated with phosphatase activity. As a superior green fertilizer, the decomposition of V. sativa can increase soil organic matter, and it also has a great capacity for nitrogen fixation [23,24]. Moreover, intercropping V. sativa could improve and maintain soil moisture, enrich soil microbial community, as well as enhance soil enzyme activities related to nutrient utilization.…”
Section: Soil Nutrientmentioning
confidence: 99%
“…sativa, in the subfamily Papilionoideae of Fabaceae, is a well-known species widely distributed in Central Asia, North Asia, Europe, and North America [21,22]. Due to its high protein content and great capacity for nitrogen fixation, it is considered as a superior forage and green fertilizer, which plays an energetic function in sustainable agriculture [23,24]. Wang et al [25] reported that V. sativa and oat intercropping had greater forage yields and economic benefits compared with the corresponding monocultures in the agro-pastoral region of China, and a sowing ratio of oat at 50% was recommended.…”
Section: Introductionmentioning
confidence: 99%